Latinomaérica en la historia de la arquitectura moderna - Fernández, Victoria (Universidad ORT Uruguay, 2018)
The present article intends to analyze the place of Latin America in the historiography of modern architecture and its evolution through time. The pioneering historians who approached this topic built the idea of a movementof universal characteristics that started from the consideration of a limited geographical area. But progressively it became more difficult to turn its back on this region of the world where modern architecture began to stand out both qualitatively and quantitatively. Selectively and inaccurately, this region began to interfere in a historiographic production whose origin was mainly European and North American. The place of Latin America in these stories grew significantly, after evidencing the crisis of modern architecture as the pioneers had conceived it. From the Latin American area itself, a historiography began to be developed that aimed to understand its architecture from the consideration of local particularities, and in the international scope reviews were made of official histories that progressively mitigated the biased center-periphery view, under which until then the architecture of the region had been considered.